ENGINEERED POLYMER IN BONE-TARGETED CELL DELIVERY - Safarova, Yuliya (Nazarbayev University School of Engineering and Digital Sciences, 2021)
Osteoporosis is a progressive system skeletal disease associated with the decreased bone mineral density and disrupted microarchitecture of the bone tissue that facilitates fragility and risk of fractures. In osteoporotic conditions the reduction in bone density and strength occurs due to the elevated osteoclastic activity and the diminished number of the osteoblast progenitor cells - mesenchymal stem cells (MSCs). This dissertation is focused on the evaluation of the new approach in cell therapy with membrane engineered MSCs that display covalently-coupled synthetic osteophilic polymers to restore the osteoblast progenitor pool and, at the same time, to inhibit osteoclastic activity in the fracture zones of the osteoporotic bones. The primary active sites of the polymer are bisphosphonate functional groups that target hydroxyapatite molecules (HA) on the bone surface and inhibit osteolysis. N-hydroxysuccinimide (NHS) groups on the other end of the molecule allow the polymer to covalently bind to MSCs’ plasma membrane components. The polymer did not affect MSCs proliferation and osteogenic differentiation while inhibiting phagocytic activity of the bone marrow derived macrophages in vitro. The therapeutic potential of the polymermodified MSCs was studied in female rats with the experimentally induced ulna fractures and estrogen-dependent osteoporosis. The osteoporosis was induced by the ovariectomy (OVX). MicroCT morphometry and histology analysis were used to determine the effect of the injected MSCs on the bone healing. Intravital analysis of the bone density dynamics in the zone of ulna fracture showed a significant increase (27.4% and 21.5%) in BMD at 4 and 24 weeks respectively after theosteotomy of the ulna in the group of animals receiving 4 transplantations (1 million cells, once per week) of the MSC modified with the polymer. The results of the intravital observations were confirmed by post-mortem analysis of the histological slices of the fracture zones.
Keywords: osteoporosis; mesenchymal stem cells; MSCs; N-hydroxysuccinimide; NHS; hydroxyapatite molecules; HA; OVX; type of access: open access